A Multicenter Study on Clinical Outcomes of Infections within 200 Days of Liver Transplantation among Recipients Age 65 Years and Older. (4th October 2017) - Malinis, Maricar; Ngo, Tue; Garcia-Diaz, Julia; Taimur, Sarah; Mueller, Nicolas; Eid, Albert; Vergidis, Pascalis; Pursell, Kenneth; Bhaskaran, Archana; La Hoz, Ricardo; Bran, Andres; Lee, Dong; et al.
Abstract: Background: Liver transplantation is increasingly performed in patients aged ≥65 years. Per the United Network for Organ Sharing data, infections are the leading primary and contributory cause of death in older liver transplant (LT) recipients. This study aims to describe the epidemiology and outcomes of infections within the first 200 days of LT in older adults. Methods: We performed a retrospective, observational multi-center study of patients aged ≥65 years who underwent primary LT from January 1, 2010 to June 30, 2015. Data collection included patient demographics, co-morbidities, transplant data, infection event in 200 days of LT and death. Severe infection was defined as the presence of sepsis, septic shock, or sepsis with multi-organ failure. Results: A total of 255 patients met inclusion criteria with median follow-up of 690 days (range 1– 2095). The mean age was 67.6 years (SD 2.4). Majority were male (67%) and white (85%). Frequent indications of LT were hepatocellular carcinoma (46%) and hepatitis C (32%). The median MELD score at the time of LT was 22 (range 6–47). Only 3% of recipients received thymoglobulin for induction. Acute rejection within 200 days of LT occurred in 31 (12%); graft failure in 8 (3%); and re-transplantation in 5 (2%). One hundred twenty-seven patients (50%) developed 274 infections; 63 (25%) had 1 infection and 64 (25%) had ≥ 2 infections. Median time to first infection after LT was 26 days [IQR 9–72]. Out of 274 infections, 182 (66%) occurred in <90 days. Severe infection occurred in 40/127 (31%). Cystitis (16%), colitis (12%), and pneumonia (11%) were common. Bacterial, viral, and fungal infections were 61%, 22%, and 7%, respectively. Common bacterial pathogens were Enterococcus sp. (15%), Clostridium difficile (12%) and E. coli (8%). Thirty-five (13%) opportunistic infections (OI) occurred due to Cytomegalovirus [CMV] (26), Candida (4), Cryptococcus (3), HHV-8 (1), and Aspergillus (1). Mortality due to infection was 3%, while all-cause mortality was 12%. Frequency of discharge to sub-acute or extended care facility after infection was 23%. Conclusion: Infections are common in this older LT cohort and occurred mainly in the early post-LT period. OIs were infrequent except for CMV. Despite concerns for immunosuppression and immunosenescence, the outcome of infection within the 200 days of LT was overall favorable. Disclosures: All authors: No reported disclosures.